Process for the preparation of electrolyte and electrolytic copper foil for high-silicon negative electrode batteries

CN122879774APending Publication Date: 2026-10-09GUANGDONG FINE YUAN SCI TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611156553.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]本发明所要解决的技术问题,是克服现有高抗拉电解铜箔“高强必脆”,即抗拉强度提升时,虽MIT耐折度可能同步上升,但代表极致抗弯折能力的180°弯折强度却急剧下降的技术偏见

Benefits of technology

1.通过限定结构调整剂包括经环氧丙烷改性的硫脲基苯并咪唑衍生物、四氢噻唑硫酮和季铵盐,可诱导铜箔沉积形成细晶与韧性柱状晶共存的特定异质结构,同步提升铜箔抗拉强度与耐弯折韧性,解决高硅负极极片内层卷绕脆断问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879774A_ABST
    Figure CN122879774A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of copper foil, in particular to an electrolyte and a preparation method of electrolytic copper foil for high-silicon negative electrode battery, wherein the total weight of the electrolyte is 1000 parts, and the components include the following parts: 90-130 parts of sulfuric acid, 0.015-0.040 parts of gelatin, 0.005-0.015 parts of collagen peptide, 0.0025-0.008 parts of structure adjusting agent, 0.015-0.045 parts of crystal refining agent, 0.002-0.010 parts of stabilizing agent, 0.001-0.005 parts of flexible agent, 0.020-0.035 parts of Cl, and water to make up the rest. ‑ 0.020-0.035 parts of Cl, and water to make up the rest. The tensile strength of the copper foil prepared by the present application is greater than or equal to 600 MPa, the elongation rate is greater than or equal to 6.0%, the MIT folding (135° / 9.8N) frequency is greater than or equal to 80 times, and the 180° bending strength is greater than or equal to 500 MPa. The copper foil has both ultra-high tensile strength and excellent bending toughness, and can effectively overcome the brittle fracture problem of the innermost layer of high-silicon electrode sheet during winding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of copper foil technology, specifically to a method for preparing an electrolyte and electrolytic copper foil for high-silicon negative electrode batteries. Background Technology

[0002] With the rapid iteration of new energy vehicles and high-end consumer electronics, the demand for energy density in lithium batteries continues to rise, making high-silicon anodes (SiOx / Si / C composites) the mainstream technology in the industry. However, silicon-based materials expand in volume by more than 250% during charging and discharging, posing a severe mechanical challenge to the copper current collector in the anode: it needs both ultra-high tensile strength to withstand expansion stress and excellent bending toughness to adapt to the inner layer of the battery cell winding (bending radius R < 1.5 mm). Currently, lithium battery copper foil generally suffers from the contradiction of "high strength inevitably leads to brittleness." Conventional copper foil has a tensile strength of only 300-350 MPa, while high-strength copper is prone to brittle fracture, making it difficult to meet the application requirements of high-silicon anodes.

[0003] Chinese invention patent CN111254464B discloses a method for preparing high-tensile-strength ultrathin electrolytic copper foil. By using compound additives such as sulfur-containing compounds and nonionic surfactants, copper foil with a tensile strength of 400-480 MPa and an elongation of 3.5-8.5% is prepared, achieving a balance between strength and elongation to some extent. However, existing copper foils still fall short in simultaneously meeting the stringent requirements of ultra-high tensile strength (>600 MPa) and excellent bending toughness (180° bending strength >500 MPa) during the drastic volume change (>250%) of high-silicon anodes during charging and discharging, and the ultra-small bending radius (R<1.5 mm) of the cell electrodes. The main challenge is the inherent technical dilemma of "high strength inevitably leads to brittleness." This invention aims to simultaneously solve these problems by introducing specific structure-adjusting agents to induce the formation of a heterogeneous structure where fine-grained and tough columnar crystals coexist. Summary of the Invention

[0004] The technical problem this invention aims to solve is to overcome the inherent bias in existing high-tensile electrolytic copper foils, where "high strength inevitably leads to brittleness." This means that while the tensile strength may increase with a corresponding increase in mitted tensile strength (MIT) and folding endurance, the 180° folding strength, representing ultimate bending resistance, decreases sharply. This invention aims to provide an electrolyte and preparation method that enables the produced copper foil to maintain an ultra-high tensile strength of ≥600MPa and an MIT folding endurance (135° / 9.8N) of ≥80 cycles, while simultaneously maintaining a 180° folding strength above 500MPa. In other words, by breaking through the conventional single-dimensional performance of "high tensile strength-high folding endurance," it simultaneously achieves "extremely high bending toughness," thus meeting the stringent requirement of preventing brittle breakage during the winding of the innermost ultra-small radius (R<1.5mm) of high-silicon anode sheets.

[0005] The first aspect of this invention provides an electrolyte comprising, based on 1000 parts by weight of the total electrolyte, the following components in parts by weight: 90-130 parts sulfuric acid, 0.015-0.040 parts gelatin, 0.005-0.015 parts collagen peptides, 0.0025-0.008 parts structure modifier, 0.015-0.045 parts crystallizer, 0.002-0.010 parts stabilizer, 0.001-0.005 parts flexibility agent, and Cl... - 0.020-0.035 parts, water to make up the balance; the structure modifier includes nitrogen-containing heterocyclic compounds and sulfur-containing heterocyclic compounds.

[0006] Existing lithium-ion battery copper foil technology suffers from the contradiction of "high strength inevitably leading to brittleness." Conventional additives can only optimize a single mechanical property and cannot adapt to the extreme bending conditions of high-silicon anodes, making it difficult to induce the formation of tough grains. This invention discovers that by limiting the structure modifiers to include propylene oxide-modified thiourea-benzimidazole derivatives, tetrahydrothiazolium thiophene, and quaternary ammonium salts, a specific heterogeneous structure can be induced in copper foil deposition, forming a coexistence of fine grains and tough columnar crystals. This simultaneously improves the tensile strength and bending toughness of the copper foil, solving the problem of brittle fracture of the inner layer of high-silicon anode sheets. The propylene oxide-modified thiourea-benzimidazole derivatives are strongly adsorbed onto the active sites of copper deposition, precisely controlling the grain growth direction and achieving grain refinement. The synergistic effect of tetrahydrothiazolium thiophene and quaternary ammonium salts induces the formation of a large number of tough columnar crystal structures during copper foil deposition, exhibiting a high Schmidt factor value, thereby improving grain slip deformation ability and enhancing toughness, fundamentally breaking through the technical bottleneck of high strength and bending resistance.

[0007] This invention, by further specifying the combined use of gelatin and collagen peptides, can refine copper foil grains, improve the uniformity of the deposition layer, significantly increase the elongation and corner folding times of the copper foil, and reduce the probability of brittle fracture. Gelatin, a macromolecular colloid, preferentially adsorbs onto the copper foil deposition surface, inhibiting abnormal grain growth and forming a uniform fine-grained structure, avoiding brittle defects caused by coarse grains. Collagen peptides, small-molecule peptides, can embed into the intergranular spaces, relieving localized internal stress during the deposition process and filling microstructural defects. The combined use of these two ingredients synergistically optimizes the internal grain arrangement of the copper foil, enhances the intergranular bonding force, and significantly improves the ductility and bending stability of the copper foil.

[0008] The crystallizing agent comprises sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and butynediol ethoxylate, wherein the weight ratio of sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and butynediol ethoxylate is (5-12):(1-3):1.

[0009] Optionally, the weight ratio of the sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and butynediol ethoxylate is (8-12):(1-3):1.

[0010] This invention specifies that the crystal-refining agent comprises sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and butynediol ethoxylate in a weight ratio of (5-12):(1-3):1. This improves the surface smoothness and deposition uniformity of copper foil, avoids stress concentration caused by surface defects, and ensures stable and compliant mechanical properties of the copper foil. Sodium polydisulfide dipropane sulfonate has a strong leveling and brightening effect, preferentially adsorbing onto protrusions on the copper foil surface, inhibiting protrusion growth, and rapidly leveling the surface microstructure. Sodium 3-mercapto-1-propane sulfonate assists in refining grains, reducing surface defects such as pinholes and pits. Butynediol ethoxylate maintains the uniform dispersion of the crystal-refining agent components in the electrolyte, avoiding local concentration imbalances. The three components work synergistically in a specific ratio, balancing the surface quality and internal structural uniformity of the copper foil, laying the foundation for excellent mechanical properties.

[0011] The structure modifier comprises a propylene oxide-modified thiourea-benzimidazole derivative, a tetrahydrothiazolium thione, and a quaternary ammonium salt, wherein the weight ratio of the propylene oxide-modified thiourea-benzimidazole derivative, the tetrahydrothiazolium thione, and the quaternary ammonium salt is 2:(0.5-1.5):(0.05-0.8).

[0012] Optionally, the weight ratio of the propylene oxide-modified thiourea-benzimidazole derivative, tetrahydrothiazothione, and quaternary ammonium salt is 2:(0.8-1.2):(0.1-0.5).

[0013] The stabilizer includes polyethylene glycol, ethylenediaminetetraacetic acid (EDTA), and polyacrylamide, wherein the weight ratio of polyethylene glycol, EDTA, and polyacrylamide is (0.5-5):(2-8):4.

[0014] Optionally, the weight ratio of polyethylene glycol, ethylenediaminetetraacetic acid and polyacrylamide is (1-5):(2-5):4.

[0015] Optionally, the number average molecular weight of the polyethylene glycol is 4000-8000.

[0016] This invention specifies that the stabilizer comprises polyethylene glycol, ethylenediaminetetraacetic acid (EDTA), and polyacrylamide in a weight ratio of (0.5-5):(2-8):4. This stabilizer enhances the density and structural stability of the copper foil deposition layer, significantly improves the tensile strength of the copper foil, and resists the severe volume expansion stress during charging and discharging of the high-silicon anode. Polyethylene glycol improves the wettability of the electrolyte and the cathode surface, promoting uniform migration and deposition of copper ions and preventing the deposition layer from becoming loose and porous. EDTA acts as a complexing agent, complexing trace metal impurities in the electrolyte and preventing impurities from embedding into the copper foil and forming stress weak points. Polyacrylamide enhances the bonding force between particles within the deposition layer, improving structural density. The three components synergistically construct a dense, impurity-free internal structure for the copper foil, strengthening its mechanical load-bearing capacity and adapting it to the high-stress conditions of the high-silicon anode.

[0017] The flexibility agent comprises sodium N-(3-sulfopropyl)-saccharin and fatty amine ethoxysulfonate, wherein the weight ratio of sodium N-(3-sulfopropyl)-saccharin and fatty amine ethoxysulfonate is 1:(0.3-1.8).

[0018] Optionally, the weight ratio of the N-(3-sulfopropyl)-saccharin sodium salt to the fatty amine ethoxysulfonate is 1:(0.3-1.5).

[0019] This invention specifies that the flexibility agent comprises sodium N-(3-sulfopropyl)-saccharin and aliphatic amine ethoxysulfonate in a weight ratio of 1:(0.3-1.8). This effectively releases internal stress during copper foil deposition, inhibits crack initiation and propagation, significantly improves the 180° bending strength of the copper foil, and prevents bending fracture. Sodium N-(3-sulfopropyl)-saccharin adsorbs at the copper foil deposition interface, weakening the accumulation of internal stress between grain interfaces and alleviating lattice distortion during deposition. The aliphatic amine ethoxysulfonate penetrates into micro-cracks in the deposition layer, passivating crack tips and preventing further crack extension. The two work synergistically in proportion, addressing both stress source resolution and crack inhibition, thus solving the problem of brittle fracture caused by internal stress and significantly improving the bending toughness of the copper foil.

[0020] The second aspect of the present invention provides a method for preparing electrolytic copper foil for high-silicon negative electrode batteries, comprising the following steps: dissolving copper wire in the electrolyte and conveying it to a foil-making machine for electrolytic foil production to obtain copper foil.

[0021] The cathode roller has a surface roughness Ra≤0.2μm and an electrode spacing of 12 mm.

[0022] Cu in the electrolyte during electrolysis 2+ The content is 70-120 parts (based on a total electrolyte weight of 1000 parts by weight).

[0023] The temperature of the electrolyte is 40-60℃.

[0024] The flow rate of the conveyed volume is 45-70 m³ / h. 3 / h.

[0025] The current density of the electrolysis is 4000-7000 A / m. 2 .

[0026] Optionally, during electrolysis, the Cu in the electrolyte... 2+ The content is 80-120 parts.

[0027] Optionally, the temperature of the electrolyte is 50-60°C.

[0028] Optionally, the flow rate of the conveyed material is 55-70 m³ / h. 3 / h.

[0029] Optionally, the current density of the electrolysis is 4700-6000 A / m. 2 .

[0030] This invention specifies Cu for electrolytic foil fabrication. 2+ The content, temperature, flow rate, and current density ensure a stable and controllable copper foil deposition process, resulting in a tensile strength ≥600MPa, elongation ≥6.0%, folding strength ≥80 times, and 180° bending strength ≥500MPa. Specific Cu... 2+ The concentration ensures a sufficient and uniform supply of copper ions, preventing uneven deposition or abnormal grains due to insufficient ions; an electrolyte temperature of 40-60℃ increases ion migration rate, optimizes grain growth kinetics, and adapts to the temperature requirements induced by tough columnar crystals; 45-70m 3 A delivery flow rate of 3000-6000 A / m² maintains uniform electrolyte component concentration, preventing local additive concentration deviations from affecting the deposition structure; a current density of 3000-6000 A / m² regulates the copper foil deposition rate, matching the rate requirement for the formation of tough columnar crystals induced by structure modifiers. The synergistic effect of multiple parameters constructs a stable electrolytic deposition environment, providing crucial preparation assurance for the formation of the target microstructure and excellent mechanical properties of the copper foil.

[0031] Beneficial effects 1. By using structure modifiers including propylene oxide-modified thiourea-benzimidazole derivatives, tetrahydrothiazothione, and quaternary ammonium salts, copper foil can be induced to form a specific heterogeneous structure in which fine grains and tough columnar grains coexist, thereby simultaneously improving the tensile strength and bending toughness of the copper foil and solving the problem of brittle fracture of the inner layer of high-silicon anode sheets.

[0032] 2. This invention limits the use of a specific ratio of gelatin and collagen peptides, which can refine the copper foil grains, improve the uniformity of the deposited layer, significantly increase the elongation and number of corner folds of the copper foil, and reduce the probability of brittle fracture.

[0033] 3. The crystallizing agent specified in this invention includes sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and butynediol ethoxylate in a weight ratio of (5-12):(1-3):1, which can improve the surface smoothness and deposition uniformity of copper foil, avoid stress concentration caused by surface defects, and ensure that the mechanical properties of copper foil are stable and meet the standards.

[0034] 4. The stabilizer specified in this invention includes polyethylene glycol, ethylenediaminetetraacetic acid and polyacrylamide in a weight ratio of (0.5-5):(2-8):4, which can enhance the density and structural stability of the copper foil deposition layer, significantly improve the tensile strength of the copper foil, and resist the severe volume expansion stress during the charging and discharging of the high silicon negative electrode.

[0035] 5. The present invention specifies that the flexibility agent includes N-(3-sulfopropyl)-saccharin sodium salt and fatty amine ethoxysulfonate in a weight ratio of 1:(0.3-1.8), which can effectively release the internal stress during the copper foil deposition process, inhibit crack initiation and propagation, significantly improve the 180° bending strength of the copper foil, and avoid bending breakage.

[0036] 6. The core design concept of this invention to achieve the above-mentioned asymmetric performance combination (high MIT flexural strength + ultra-high 180° bending strength) lies in the following: In conventional understanding, refining grains with additives can improve tensile strength, and tensile strength and MIT flexural strength (mainly reflecting the material's ability to resist repeated folding fatigue) are positively correlated within a certain range. However, an overly refined structure will significantly reduce the material's 180° bending strength (reflecting the material's resistance to fracture under a single large-angle bend) because its grain boundaries are dense and dislocation pile-up is severe, making it prone to cracking along the grain boundaries during severe bending.

[0037] This invention revolutionizes copper foil deposition by inducing a heterogeneous multilayer structure of "fine-grained base layer + tough columnar grains" through specific structure modifiers (especially propylene oxide-modified thiourea-benzimidazole derivatives in synergy with tetrahydrothiazolium thione and quaternary ammonium salts). The fine grains and tough columnar grain boundaries provide ultra-high tensile strength and effectively enhance grain slip capability, giving the copper foil excellent resistance to cyclic folding (i.e., high MIT folding endurance). The coarse columnar grains growing along the thickness direction act as a "tough skeleton," coordinating local plastic deformation through intragranular slip during 180° bending, preventing crack initiation and propagation, thereby significantly improving 180° bending strength. Ultimately, this achieves a breakthrough in tensile strength and MIT folding endurance, exceeding 500 MPa at 180° bending strength, completely breaking the traditional constraint that "high-strength copper foil is not resistant to large-angle bending." Attached Figure Description

[0038] Figure 1 This is an EBSD cross-sectional image of the electrolytic copper foil product obtained in Example 1.

[0039] Figure 2 This is a graph showing the calculated Schmidt factor (SF) of the cross-section of the electrolytic copper foil product obtained in Example 1. Detailed Implementation

[0040] The raw materials used in the following examples and comparative examples are shown in Table 1. Components not listed are not limited to specific manufacturers: Table 1

[0041] Example 1 An electrolyte comprises the following components at the following concentrations: 110 parts sulfuric acid, 0.025 parts gelatin, 0.008 parts collagen peptides, 0.006 parts structure modifier, 0.035 parts crystallizer, 0.007 parts stabilizer, 0.003 parts flexibility agent, and Cl... - 0.035 parts, water to make up the balance; the Cl - Provided by hydrochloric acid.

[0042] The crystallizing agent is sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and butynediol ethoxylate, wherein the weight ratio of sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and butynediol ethoxylate is 10:2:1.

[0043] The structure modifier is a propylene oxide-modified thiourea-benzimidazole derivative, tetrahydrothiazolium thione, and quaternary ammonium salt, wherein the weight ratio of the propylene oxide-modified thiourea-benzimidazole derivative, tetrahydrothiazolium thione, and quaternary ammonium salt is 2:1:0.2.

[0044] The preparation method of the propylene oxide-modified thiourea-benzimidazole derivative comprises the following steps: 1 mol of 2-mercaptobenzimidazole is dissolved in 10 L of isopropanol, 1.2 mol of propylene oxide and 0.01 mol of triethylamine are added, and the mixture is stirred at 50 °C for 6 hours. After the reaction is completed, the solvent is removed by vacuum distillation, and the resulting solid is recrystallized from ethanol and dried under vacuum to obtain a white crystalline product, which is the propylene oxide-modified thiourea-benzimidazole derivative. The structure is confirmed by elemental analysis and infrared spectroscopy.

[0045] The stabilizer is polyethylene glycol, ethylenediaminetetraacetic acid (EDTA), and polyacrylamide, wherein the weight ratio of polyethylene glycol, EDTA, and polyacrylamide is 1:5:4.

[0046] The flexibility agent is N-(3-sulfopropyl)-saccharin sodium salt and fatty amine ethoxysulfonate, and the weight ratio of N-(3-sulfopropyl)-saccharin sodium salt to fatty amine ethoxysulfonate is 1:0.7.

[0047] A method for preparing electrolytic copper foil for high-silicon anode batteries includes the following steps: dissolving copper wire in the electrolyte and feeding it into a foil-making machine (cathode roller surface roughness Ra≤0.2μm, electrode spacing: 12 mm) for electrolytic foil production to obtain copper foil.

[0048] Cu in the electrolyte during electrolysis 2+ The content is 90 parts; the temperature of the electrolyte is 55°C; the flow rate of the conveying is 65m³. 3 / h; the current density of the electrolysis is 4700 A / m 2 .

[0049] Example 2 The specific implementation method is the same as in Example 1; the difference is that the flow rate of the conveyed volume is 55m³. 3 / h.

[0050] Example 3 The specific implementation method is the same as in Example 1; the difference is that the temperature of the electrolyte is 50°C.

[0051] Example 4 The specific implementation method is the same as in Example 1; the difference is that the flow rate of the conveyed volume is 70m³. 3 / h; the current density of the electrolysis is 4000 A / m 2 .

[0052] Example 5 The specific implementation method is the same as in Example 1; the difference is that the temperature of the electrolyte is 60°C; and the Cu in the electrolyte during electrolysis... 2+ The content is 80 parts.

[0053] Example 6 The specific implementation method is the same as in Example 1; the difference is that the concentration of sulfuric acid in the electrolyte is 90 parts; and the electrolysis current density is 6000 A / m. 2 .

[0054] Example 7 The specific implementation method is the same as in Example 1; the difference is that the Cu in the electrolyte during electrolysis... 2+ The content is 120 parts; the electrolyte contains Cl - The concentration was 0.020 parts.

[0055] Example 8 The specific implementation method is the same as in Example 1; the difference is that the electrolyte contains: 110 parts sulfuric acid and 0.015 parts gelatin.

[0056] Example 9 The specific implementation method is the same as in Example 1; the difference is that the electrolyte contains: Cl - 0.035 parts, collagen peptides 0.005 parts.

[0057] Example 10 The specific implementation method is the same as in Example 1; the difference is that the electrolyte contains: 0.030 parts gelatin and 0.0025 parts structure modifier.

[0058] Example 11 The specific implementation method is the same as in Example 1; the difference is that the electrolyte contains: 0.010 parts of collagen peptide and 0.020 parts of crystallizer.

[0059] Example 12 The specific implementation method is the same as in Example 1; the difference is that the electrolyte contains: 0.008 parts of structure modifier and 0.005 parts of stabilizer.

[0060] Example 13 The specific implementation method is the same as in Example 1; the difference is that the electrolyte contains: 0.045 parts of crystal-refining agent and 0.001 parts of flexible agent.

[0061] Example 14 The specific implementation method is the same as in Example 1; the difference is that the electrolyte contains 0.010 parts of stabilizer.

[0062] Example 15 The specific implementation method is the same as in Example 1; the difference is that the electrolyte contains 0.005 parts of a flexibility agent.

[0063] Comparative Example 1 The specific implementation method is the same as in Example 1; the difference is that gelatin is not added to the electrolyte.

[0064] Comparative Example 2 The specific implementation method is the same as in Example 1; the difference is that collagen peptides are not added to the electrolyte.

[0065] Comparative Example 3 The specific implementation method is the same as in Example 1; the difference is that no structure modifier is added to the electrolyte.

[0066] Comparative Example 4 The specific implementation method is the same as in Example 1; the difference is that no crystal-refining agent is added to the electrolyte.

[0067] Comparative Example 5 The specific implementation method is the same as in Example 1; the difference is that no stabilizer is added to the electrolyte.

[0068] Comparative Example 6 The specific implementation method is the same as in Example 1; the difference is that no flexible agent is added to the electrolyte.

[0069] Comparative Example 7 The specific implementation method is the same as in Example 1; the difference is that the Cu in the electrolyte during electrolysis... 2+ The content is 65 parts.

[0070] Comparative Example 8 The specific implementation method is the same as in Example 1; the difference is that the concentration of sulfuric acid in the electrolyte is 70 parts.

[0071] Comparative Example 9 The specific implementation method is the same as in Example 1; the difference is that the electrolyte contains Cl - The concentration was 0.004 parts.

[0072] Comparative Example 10 The specific implementation method is the same as in Example 1; the difference is that the flow rate of the conveyed volume is 40m³. 3 / h.

[0073] Comparative Example 11 The specific implementation method is the same as in Example 1; the difference is that the temperature of the electrolyte is 30°C.

[0074] Comparative Example 12 The specific implementation method is the same as in Example 1; the difference is that the current density of the electrolysis is 2500 A / m. 2 .

[0075] Comparative Example 13 The specific implementation method is the same as in Example 1; the difference is that the weight ratio of the propylene oxide-modified thiourea-benzimidazole derivative, tetrahydrothiazothione and quaternary ammonium salt is 2:1:1.

[0076] Comparative Example 14 The specific implementation method is the same as in Example 1; the difference is that thiourea is used instead of the propylene oxide-modified thiourea-based benzimidazole derivative.

[0077] Comparative Example 15 The specific implementation method is the same as in Example 1; the difference is that the weight ratio of sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate and butynediol ethoxylate is 3:1:1.

[0078] Comparative Example 16 The specific implementation method is the same as in Example 1; the difference is that sodium thiazolinyl dithiopropane sulfonate is used instead of sodium polydithiopropane sulfonate.

[0079] Comparative Example 17 The specific implementation method is the same as in Example 1; the difference is that the weight ratio of polyethylene glycol, ethylenediaminetetraacetic acid and polyacrylamide is 3:1:2.

[0080] Comparative Example 18 The specific implementation method is the same as in Example 1; the difference is that polyvinyl alcohol is used instead of polyethylene glycol.

[0081] Comparative Example 19 The specific implementation method is the same as in Example 1; the difference is that the weight ratio of the N-(3-sulfopropyl)-saccharin sodium salt and the fatty amine ethoxysulfonate is 1:2.

[0082] Performance testing methods 6-micron copper foil was prepared according to the methods in the examples and comparative examples. The tensile strength and elongation of the copper foil were tested according to the test methods in GB / T 29847-2013. The MIT (mitigation tolerance) of the copper foil (135° / 9.8N) was tested according to the test methods in GB / T 2679.5-2016 "Determination of folding endurance of paper and paperboard". Currently, there is no unified national standard for the 180° bending strength of copper foil. This invention adopts the following customized method, referring to GB / T 232-2010 "Metallic materials bending test method" and common practices in the lithium battery industry: a. Cut a copper foil sample that is 15mm wide and 200mm long.

[0083] b. Fold the sample 180° along the middle, ensuring the crease is tightly closed, hold for 3 seconds, and then roll it once at a uniform speed along the length of the sample using a 2 kg pressure roller.

[0084] c. Unfold the specimen and use a universal testing machine to stretch the specimen at a tensile speed of 50 mm / min. Record the maximum force F (N) when the specimen breaks along the crease.

[0085] d. Calculate the 180° bending strength σ = F / (sample width × thickness), where the width = 15 mm and the thickness is the measured copper foil thickness (e.g., 6 μm). Take the arithmetic mean of 5 valid samples as the final result.

[0086] The test data is listed in Table 2.

[0087] Performance test data Table 2

[0088] As shown in Table 2, the copper foils prepared in all embodiments of the present invention exhibit excellent and balanced mechanical properties, with tensile strength ≥600MPa, elongation ≥6.0%, MIT folding resistance (135° / 9.8N) ≥80 times, and 180° bending strength ≥500MPa, fully meeting the dual requirements of high-silicon anode batteries for ultra-high tensile strength and bending toughness of copper foil. However, due to the absence of key electrolyte components, improper ratios, component substitutions, or deviations in electrolysis process parameters, the performance of each comparative example showed varying degrees of degradation: the copper foil performance dropped drastically when crystal refiner was missing (Comparative Example 4), with tensile strength only 351MPa and elongation as low as 1.72%; the bending strength dropped to 396MPa when flexible agent was missing (Comparative Example 6), and brittleness was significantly aggravated; the copper foil performance also dropped drastically when gelatin, collagen peptides, structure modifiers, stabilizers (Comparative Examples 1–3, 5), or Cu were missing. 2+ Content, sulfuric acid concentration, Cl -Deviations in process parameters such as concentration, electrolyte temperature, flow rate, and current density from the specified range (Comparative Examples 7–12) can lead to one or more items failing to meet the standards for tensile strength, elongation, number of bends, or bending strength. Imbalances in the ratio of structure modifiers, crystal refiners, stabilizers, and flexibility agents (Comparative Examples 13, 15, 17, 19) or substitution of key components (Comparative Examples 14, 16, 18) can disrupt the synergistic formation of fine-grained and tough columnar crystal structures, resulting in "high strength but low toughness" or insufficient toughness. This demonstrates that the additive components and specific ratios in the electrolyte of this invention, along with the corresponding electrolytic process parameters, work synergistically and are indispensable. This effectively overcomes the bottleneck of "high strength inevitably leads to brittleness" in existing technologies and stably prepares high-performance electrolytic copper foil suitable for high-silicon anode batteries.

[0089] from Figure 1 As can be seen, with appropriate electrolyte additives, the copper foil contains a large number of fine grains, while large columnar crystals penetrate the entire cross-section of the copper foil. The fine grains bring more grain boundaries, effectively resisting deformation and improving the original tensile strength of the copper foil. The large columnar crystals allow for stress release and grain slippage under destructive bending and folding conditions, enhancing the overall plastic deformation capacity of the copper foil.

[0090] from Figure 2 As can be seen from the image, the "soft" orientation accounts for over 70%, and the central columnar crystal region has a large slip coefficient. When folded, it undergoes slip, and the internal dislocations travel a long distance, making them less susceptible to absorption by grain boundaries. This allows it to store a high density of dislocations, delaying necking and maintaining a certain degree of structural stability. This improves the tensile strength after deformation and endows the material with unique high-toughness properties.

Claims

1. An electrolyte, characterized in that, Based on 1000 parts by weight of the total electrolyte, it comprises the following components in parts by weight: 90-130 parts sulfuric acid, 0.015-0.040 parts gelatin, 0.005-0.015 parts collagen peptides, 0.0025-0.008 parts structure modifier, 0.015-0.045 parts crystallizer, 0.002-0.010 parts stabilizer, 0.001-0.005 parts flexibility agent, Cl... - 0.020-0.035 parts, water to make up the balance; the structure modifier includes thiourea-benzimidazole derivatives modified with propylene oxide, tetrahydrothiazothione and quaternary ammonium salts.

2. The electrolyte according to claim 1, characterized in that, The weight ratio of the propylene oxide-modified thiourea-benzimidazole derivative, tetrahydrothiazothione, and quaternary ammonium salt is 2:(0.8-1.2):(0.1-0.5).

3. The electrolyte according to claim 2, characterized in that, The crystallizing agent comprises sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and butynediol ethoxylate, wherein the weight ratio of sodium polydisulfide dipropane sulfonate, sodium 3-mercapto-1-propane sulfonate, and butynediol ethoxylate is (5-12):(1-3):

1.

4. The electrolyte according to claim 3, characterized in that, The stabilizer includes polyethylene glycol, ethylenediaminetetraacetic acid (EDTA), and polyacrylamide, wherein the weight ratio of polyethylene glycol, EDTA, and polyacrylamide is (1-3):(3-6):4; and the number average molecular weight of polyethylene glycol is 4000-8000.

5. The electrolyte according to claim 4, characterized in that, The flexibility agent comprises sodium N-(3-sulfopropyl)-saccharin and fatty amine ethoxysulfonate, wherein the weight ratio of sodium N-(3-sulfopropyl)-saccharin and fatty amine ethoxysulfonate is 1:(0.5-1.2).

6. A method for preparing electrolytic copper foil for high-silicon anode batteries, characterized in that, Includes the following steps: S1. Preparation of electrolyte: Dissolve copper material in an aqueous solution containing 90-130 parts sulfuric acid, controlling Cu²... + The content is 70-120 parts; then gelatin, collagen peptides, structure modifiers, crystallizers, stabilizers, softeners and Cl are added. - Add water to the required volume. S2. Electrolytic foil production: The electrolyte obtained in step S1 is fed to the foil production machine. The electrolyte temperature is controlled at 40-60℃, the flow rate is 45-70m³ / h, and the current density is 4000-7000A / m². Electrolytic foil production is carried out to obtain the foil. S3. Surface treatment: The obtained raw foil is washed with water, passivated and dried to obtain electrolytic copper foil for high silicon negative electrode batteries; The cathode roller of the foil-making machine has a surface roughness Ra≤0.35μm and an electrode spacing of 12mm.

7. The preparation method according to claim 6, characterized in that, Cu in the electrolyte during electrolysis 2+ The content is 70-120 parts.

8. The preparation method according to claim 6, characterized in that, The temperature of the electrolyte is 40-60℃.

9. The preparation method according to claim 6, characterized in that, The flow rate of the conveyed volume is 45-70 m³ / h. 3 / h.

10. The preparation method according to claim 6, characterized in that, The current density of the electrolysis is 4000-6000 A / m. 2 .

Citation Information

Patent Citations

  • A method for preparing ultrathin electrolytic copper foil for high tensile strength lithium-ion batteries

    CN111254464B